2020
DOI: 10.3390/molecules25235760
|View full text |Cite
|
Sign up to set email alerts
|

Euodia pasteuriana Methanol Extract Exerts Anti-Inflammatory Effects by Targeting TAK1 in the AP-1 Signaling Pathway

Abstract: Euodia pasteuriana A. Chev. ex Guillaumin, also known as Melicope accedens (Blume) T.G. Hartley, is a herbal medicinal plant native to Vietnam. Although Euodia pasteuriana is used as a traditional medicine to treat a variety of inflammatory diseases, the pharmacological mechanisms related to this plant are unclear. This study aimed to investigate the anti-inflammatory effects of a methanol extract of Euodia pasteuriana leaves (Ep-ME) on the production of inflammatory mediators, the mRNA expression of proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The activator protein-1 (AP-1) as another major transcription factor is involved in the immune response except NF-κB signaling, and c-Jun and c-Fos were the major AP-1 proteins, which can control the expression of cytokines and promote immune responses. , So we checked the expressions of c-Jun and c-Fos and found that they were increased by PSPP-1 treatment, which were significantly different in comparison to the control group ( P < 0.05) (Figure ). The TLR4/AP-1 signaling pathway is very important in macrophage activation-mediated immunity, and the active upstream factors of AP-1 such as IRAK1, TAK1, and MAPKs were regulated synchronously by PSPP-1.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The activator protein-1 (AP-1) as another major transcription factor is involved in the immune response except NF-κB signaling, and c-Jun and c-Fos were the major AP-1 proteins, which can control the expression of cytokines and promote immune responses. , So we checked the expressions of c-Jun and c-Fos and found that they were increased by PSPP-1 treatment, which were significantly different in comparison to the control group ( P < 0.05) (Figure ). The TLR4/AP-1 signaling pathway is very important in macrophage activation-mediated immunity, and the active upstream factors of AP-1 such as IRAK1, TAK1, and MAPKs were regulated synchronously by PSPP-1.…”
Section: Results and Discussionmentioning
confidence: 98%
“…The inhibition of NO production by Pd-EE was observed at the transcriptional level, since iNOS expression was attenuated ( Figure 1 ). In fact, the activity of inflammation-regulatory transcription factors NF-κB and AP-1 was strongly downregulated ( Figure 2 ), implying that these transcription factors could be targeted by Pd-EE, as shown in the cases of other medicinal plants such as Olea europaea , Phyllanthus acidus , Euodia pasteuriana , Panax ginseng , and Alisma canaliculatum [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 93%
“…In order to obtain a better understanding of the regulation of COX-2 expression by SO, we observed the level of c-Jun, as this transcription factor is a major subunit of AP-1, which plays a critical role in controlling COX-2 expression in RAW264.7 cells under LPS-stimulated conditions ( 10 ). An increased level of c-Jun was observed 45, 60, and 75 minutes after LPS treatment, while pre-treatment with SO showed a decrease in c-Jun levels, as caused by nuclear fractionation, immunofluorescence, and reporter gene assay ( Fig.…”
Section: Resultsmentioning
confidence: 99%